2010
DOI: 10.4314/afrrev.v4i1.58224
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Perspective on Road Traffic Accident Variations in Lagos Mainland, South-Western Nigeria

Abstract: The research work uncovered the fact that the problem of road traffic accidents in Lagos Mainland (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Ironically, in Nigeria, studies have indicated that an increasing number of accidents (Onakomaya, 1988; Gbadamosi, 2003;Atubi and Onokala, 2009) has accompanied better facilities in terms of good quality and standardized roads. This is contrary to the trends in countries where even the level of the sophisticated road network and the volume of vehicular traffic are higher (Atubi, 2010a(Atubi, , 2015a(Atubi, and 2020b The WHO estimates indicated 21.04 fatalities per 100,000 population. This figure is below the average of 27 fatalities per 100,000 populations estimate for African region.…”
mentioning
confidence: 72%
“…Ironically, in Nigeria, studies have indicated that an increasing number of accidents (Onakomaya, 1988; Gbadamosi, 2003;Atubi and Onokala, 2009) has accompanied better facilities in terms of good quality and standardized roads. This is contrary to the trends in countries where even the level of the sophisticated road network and the volume of vehicular traffic are higher (Atubi, 2010a(Atubi, , 2015a(Atubi, and 2020b The WHO estimates indicated 21.04 fatalities per 100,000 population. This figure is below the average of 27 fatalities per 100,000 populations estimate for African region.…”
mentioning
confidence: 72%